Differences in the impact of vocabulary processing levels on noun and verb processing in the second language and its importance in teaching english - Voronin, Maxim Valerevich (2021)
Based on the studies of language psychology, in word processing and recycling, perceptual, conceptual, syntactic coding, and phonetic patterns have been emphasized. Also, considering previous studies, theories about the sequence and synchronicity of the word processing level in phonetics, syllables, syntax, and semantics have been proposed. In this study, which was conducted with eighty-six undergraduate students of English language and literature, using the image naming test as a cognitive tool, the differences in the level of word processing in noun and verb games in the second language were investigated. According to the results of this study, in the second language, the processing of nouns is more than the level of perception, and the processing of verbs is affected by the level of regulation. As a result, teaching nouns in English makes them visible on appearance and appearance features, and in teaching verbs observation on meaningful features and characteristics.